EXPLORING ZOONYMS: LINGUISTIC AND CULTURAL SIGNIFICANCE IN HUMAN SOCIETY: EXPLORING ZOONYMS: LINGUISTIC AND CULTURAL SIGNIFICANCE IN HUMAN SOCIETY - Jadigerova, Aygul (Журнал иностранных языков и лингвистики, 2025)
Language serves not only as a medium for communication but also as a reflection of cultural identity and societal values. The term "intercultural interaction" is defined by a respectful attitude towards representatives of other cultures, the demonstration of tolerance, including racial, national, and religious tolerance, and a willingness to work in a foreign language environment [2; 214]. Within this dynamic, zoonyms—the specific names and terms used for animals—offer a window into the ways different cultures understand and relate to the animal kingdom. This exploration of zoonyms extends beyond mere nomenclature, highlighting how these terms encapsulate cultural beliefs, historical narratives, and social attitudes toward animals.